Partially anticipated events: A model of stock price reactions with an application to corporate acquisitions - Malatesta, Paul H.; Thompson, Rex (Journal of Financial Economics, 1985)
This paper presents a model of stock price reactions to partially anticipated events. The model formalizes the intuition that stock price reactions reflect both the economic importance of events and the extent to which events are surprises. Unbiased estimates of the economic importance of partially anticipated events must combine stock price reactions to events with stock price movements in periods when no event occurs. The model is used to estimate the value of acquisition attempts made by frequently acquiring firms. For a sample of thirty active acquirers, the evidence indicates that acquisition attempts were profitable investment projects.